2006
DOI: 10.1002/kin.20190
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(III) catalysis in polymerization of vinyl monomers by charge‐transfer mechanism with aminoalcohols and carbontetrachloride: A kinetic study

Abstract: The kinetics of ruthenium(III) catalyzed polymerization of vinyl monomers (M) (methyl-, ethyl-, and butylacrylates) by charge-transfer mechanism with aminoalcohols (AA) (namely, ethanol-, diethanol-, and triethanol amines) and carbontetrachloride in dimethylsulfoxide medium have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Polymerization of methylmethacrylate (MMA) initiated by amines in the presence of CCl 4 by a charge-transfer mechanism [14][15][16][17][18][19][20][21][22][23][24][25], amines, and Ru III complexes is also a very effective system in atom transfer radical polymerization mechanism [26,27], and a free-radical retrograde-precipitation polymer mechanism has been studied widely by many investigators [28][29][30][31][32][33][34][35]. It has been observed that two different mechanisms [36,37] for the initiation of polymerization of MMA, involving the charge-transfer complex formed by the interaction of amine and CCl 4 -under the conditions [CCl 4 /amine]≤1-and by the interaction of amine and MMA-under the conditions [CCl 4 /amine]≥1 have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization of methylmethacrylate (MMA) initiated by amines in the presence of CCl 4 by a charge-transfer mechanism [14][15][16][17][18][19][20][21][22][23][24][25], amines, and Ru III complexes is also a very effective system in atom transfer radical polymerization mechanism [26,27], and a free-radical retrograde-precipitation polymer mechanism has been studied widely by many investigators [28][29][30][31][32][33][34][35]. It has been observed that two different mechanisms [36,37] for the initiation of polymerization of MMA, involving the charge-transfer complex formed by the interaction of amine and CCl 4 -under the conditions [CCl 4 /amine]≤1-and by the interaction of amine and MMA-under the conditions [CCl 4 /amine]≥1 have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have been widely used as heterogeneous and homogeneous catalysts in various polymerizations3–6 and redox reactions 7–15. It has been observed that very small amounts of these metal ions (∼ 10 −6 M ) are sufficient to accelerate the rate of polymerization ( R p ) of monomers, namely, methyl acrylate (MA), ethyl acrylate (EA), butyl acrylate,16 and acrylonitrile 17. These metal ions also help in the formation of charge‐transfer complexes between amine/amino alcohols and carbon tetrachloride (CCl 4 ) or monomer and themselves; these play an important role in the initiation of the polymerization processes.…”
Section: Introductionmentioning
confidence: 99%